The speciation of dissolved zinc in the Atlantic sector of the Southern Ocean - Baars, Oliver; Croot, Peter (Deep Sea Research Part II: Topical Studies in Oceanography, 2011)
The speciation of dissolved zinc (Zn) was investigated by voltammetry in the Atlantic sector of the Southern Ocean along two transects across the major frontal systems: along the Zero Meridian and across the Drake Passage. In the Southern Ocean south of the APF we found detectable labile inorganic Zn throughout the surface waters in contrast to studies from lower latitudes. Using a combination of ASV titrations and pseudopolarography revealed the presence of significant concentration of electrochemically inert Zn ligands throughout the Southern Ocean. These ligands however were nearly always saturated due to the presence of excess concentrations of dissolved Zn that were associated with the high nutrient waters south of the Antarctic Polar Front (APF). Only in surface waters did the concentration of Zn complexing ligands exceed the dissolved Zn concentrations suggesting a biological source for these ligands. Our findings have clear implications for the biogeochemical cycling of Zn and for the interpretation of paleo records utilizing Zn in opal as a tracer of Zn speciation in the water column.